2012
DOI: 10.1038/oncsis.2012.29
|View full text |Cite
|
Sign up to set email alerts
|

DNA replication stress response involving PLK1, CDC6, POLQ, RAD51 and CLASPIN upregulation prognoses the outcome of early/mid-stage non-small cell lung cancer patients

Abstract: Lung cancer is the leading cause of cancer deaths worldwide. Clinical staging classification is generally insufficient to provide a reliable prognosis, particularly for early stages. In addition, prognostic factors are therefore needed to better forecast life expectancy and optimize adjuvant therapeutic strategy. Recent evidence indicates that alterations of the DNA replication program contribute to neoplasia from its early stages and that cancer cells are frequently exposed to endogenous replication stress. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
77
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 96 publications
(79 citation statements)
references
References 48 publications
1
77
1
Order By: Relevance
“…This novel Pol y function may be particularly important within the context of cancer, as high POLQ expression is strongly associated with poor clinical outcome of patients with colon, breast and lung cancers [22][23][24]55,56 . Abnormal temporal control of replication, recently demonstrated in several haematologic malignancies, has been proposed to represent a common mechanism responsible for genomic instability found in cancer cells 57 ; therefore, Pol y overexpression may be of cardinal importance in defining the modified temporal replication programme in cancer cells and may constitute a driving force for chromosomal instability [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel Pol y function may be particularly important within the context of cancer, as high POLQ expression is strongly associated with poor clinical outcome of patients with colon, breast and lung cancers [22][23][24]55,56 . Abnormal temporal control of replication, recently demonstrated in several haematologic malignancies, has been proposed to represent a common mechanism responsible for genomic instability found in cancer cells 57 ; therefore, Pol y overexpression may be of cardinal importance in defining the modified temporal replication programme in cancer cells and may constitute a driving force for chromosomal instability [58][59][60] .…”
Section: Discussionmentioning
confidence: 99%
“…By conducting large-scale studies of the expression of DNA replication factors in patients with colon, breast and lung cancer, we recently uncovered major alterations in the expression pattern of POLQ, the gene encoding Pol y, and discovered that excess POLQ correlates with genetic instability and poor prognosis [22][23][24] . This is, to our knowledge, the strongest link between a negative clinical outcome and the expression of a DNA polymerase 25 .…”
mentioning
confidence: 99%
“…We and others have demonstrated that Polθ expression is a strong prognostic factor in different types of cancers (Allera-Moreau et al, 2012; Lemée et al, 2010; Pillaire et al, 2010). Recent studies have demonstrated the important role of Polθ in DNA repair under stress conditions and suggest that Polθ overexpression may play a key role in mechanisms of protection against genotoxic therapies (Yousefzadeh et al, 2014), especially when other repair pathways are no longer functional (Ceccaldi et al, 2015; Mateos-Gomez et al, 2015).…”
Section: Discussionmentioning
confidence: 84%
“…To explore whether POLQ deregulation in cancer could be part of a global deregulation of genes involved in the response of replicative stress, we thought to go back to our previously reported real-time PCR data related to DNA samples from breast, colorectal or lung cancer patients (Allera-Moreau et al, 2012; Lemée et al, 2010; Pillaire et al, 2010), and address whether the expression of POLQ was correlated with the expression of other genes. By using Pearson coefficient of correlation with a threshold of P =0.65, we searched for genes that significantly correlated with POLQ expression.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation